The Protection of Crocin Against Ulcerative Colitis and Colorectal Cancer via Suppression of NF-κB-Mediated Inflammation - Teng, Shanshan; Hao, Jie; Bi, Hui; Li, Congcong; Zhang, Yongfeng; Zhang, Yaqin; Han, Weiwei; Wang, Di (Frontiers in Pharmacology, 2021)
Background: In China, the incidence of ulcerative colitis (UC) is increasing every year, but the etiology of UC remains unclear. UC is known to increase the risk of colorectal cancer (CRC). The aim of this study was to investigate the protective effects of crocin against UC and CRC in mouse models. Methods: Crocin was used to treat the dextran sodium sulfate (DSS)-induced UC mice for 3 weeks, and ApcMinC/Gpt mice with CRC for 8 weeks. Proteomics screening was used to detect changes in the protein profiles of colon tissues of UC mice. Enzyme-linked immunosorbent assays and western blot were used to verify these changes. Results: Crocin strongly reduced the disease activity index scores of UC mice, and improved the pathological symptoms of the colonic epithelium. The anti-inflammatory effects of crocin were indicated by its regulation of the activity of various cytokines, such as interleukins, via the modulation of nuclear factor kappa-B (NF-κB) signaling. Crocin significantly suppressed tumor growth in ApcMinC/Gpt mice and ameliorated pathological alterations in the colon and liver, but had no effects on spleen and kidney. Additionally, crocin significantly decreased the concentrations of interleukins and tumor necrosis factor-α in the sera and colon tissues, suggesting its anti-inflammatory effects related to NF-κB signaling. Finally, 12-h incubation of SW480 cells with crocin caused cell cycle arrest, enhanced the apoptotic rate, promoted the dissipation of mitochondrial membrane potential, and the over-accumulation of reactive oxygen species. From the theoretical analyses, phosphorylated residues on S536 may enhance the protein-protein interactions which may influence the conformational changes in the secondary structure of NF-κB. Conclusion: The protective effects of crocin on UC and CRC were due to its suppression of NF-κB-mediated inflammation.